Investigating the experiences of medical students quarantined due to COVID-19 exposure - Han, Sallie; Kim, Iris; Rojas, David; Nyhof-Young, Joyce (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2023)
Background: The COVID-19 pandemic profoundly impacted medical education systems worldwide. Between March 2020 and December 2021, 111 MD students at the University of Toronto completed two-week quarantines due to hospital or community exposures and experienced disrupted clinical instruction. We explored the experiences, barriers, and supports of these quarantined medical students to identify program development opportunities and improve student supports.Methods: We used a qualitative descriptive approach to explore experiences of clerkship students quarantined due to COVID-19 exposure. Methods included an online survey with open-ended questions and an audio-recorded interview. We analysed the demographic survey responses using descriptive statistics. Subsequently, we conducted descriptive thematic analysis of the narrative survey responses and transcribed interview recordings.Results: Concerns reported in surveys (n = 23, response rate 20.7%) and interviews (n = 5) included themes of illness uncertainty, racial tensions, confidentiality of COVID-19 status, unclear academic expectations, and financial burden. Supports included friends, family, and MD program administration. Recommendations related to communication, administration, equity considerations, supports, confidentiality/privacy, and academics.Conclusion: Supporting student wellbeing and learning is at the core of medical training. Enhanced understanding of health profession trainee needs during COVID can improve institutional supportive responses to students routinely and during times of crisis.